The Role of Relatives in Caring for Patients with Acute Stroke - Pileckaja, Jelene; Kuzborska, Zyta (Slauga. Mokslas ir praktika, 2020)
Due to high mortality and severe residual disability, stroke is one of the most important medical and social problems in the world. According to research, family support and motivation in acute period of the disease result in better treatment outcomes and recovery of impaired functions. Aim of the research: To identify the role of relatives in caring for patients with acute stroke. The research was conducted in X unit of a Vilnius city hospital where patients with cerebral circulation disorders were treated. Research method: a questionnaire survey. The study involved 40 respondents who had relatives with acute stroke. Research results and conclusions. Most of the relatives know that stroke is an acute disorder of cerebral circulation and that it can cause disability. However, their knowledge on stroke risk factors is insufficient; the respondents were best informed about such risk factors as age and high blood pressure, and worst informed about diabetes mellitus and obesity. Most of them indicated that the care of a hospitalized patient with acute stroke should be provided by medical personnel as well as by relatives and that low activity of relatives in caring for patients was predetermined by the lack of their knowledge and skills. Relatives of patients with acute stroke were in need of information on different subjects related to treatment, nursing and care. More than 2/3 of the respondents specified they would attend training on post-stroke care.